Kyai NU’s Patrons as an Agent of Social Change and Environmental Marine Conservation: A Case Study in Paciran Lamongan - Ahmad Imron Rozuli; Muhamad Yasin; Moh. Anas Kholish; Abd. Rahman Ambo’ Dalle (ADDIN, 2022)
This article aims to examine the patrons of NU’s Kyai as an agent of social change, as well as environmental conservation in the coastal communities of Lamongan through a green fatwa on the prohibition of destructive fishing. The research method used in this study is qualitative descriptive research with techniques for collecting in-depth interview data, participant observation, and FGD, as well as documentation. The results of this article research study show that NU’s Kyai plays a significant role in carrying out social changes in the Lamongan coastal community. The role of social change in NU and environmental conservation is expressed through green fatwas on the preservation of marine ecosystems by banning destructive fishing gear. NU’s Kyai who are considered authoritative patrons of the Lamongan coastal community base their social construction on priority jurisprudence considerations, namely by prioritizing general and long-term benefits, rather than special benefits and benefits that are short-term. According to the NU’s Kyai, preserving marine ecosystems by prohibiting destructive fishing gear is a general and long-term benefit that must be prioritized, rather than the welfare of a handful of fishing vessels with destructive tools.